2017
DOI: 10.21276/aimdr.2017.3.2.og1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcome in Eclampsia

Abstract: Background: (1)To study maternal outcome in eclampsia in relation to respiratory complications, fever, DIC, renal system affection and electrolyte imbalance. (2) To study the fetal outcome in eclampsia in relation to small for gestational age, intrauterine death, neonatal mortality, perinatal mortality and need for NICU admission.Study Design: It was a crosssectional prospective study conducted at Government Medical College Nagpur over a period of 3 months (14 May to 14 July). Methods: The study was approved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…6.4% of patients had DIC which is similar to study by Agrawal M et al showed 6.97 % of DIC in their study. 13 Incidence of Hellp syndrome was 17.7% in our study which is similar to study by Kumari S et al from Andhra Pradesh who reported 18% of Hellp syndrome in their study.…”
Section: Discussionsupporting
confidence: 90%
“…6.4% of patients had DIC which is similar to study by Agrawal M et al showed 6.97 % of DIC in their study. 13 Incidence of Hellp syndrome was 17.7% in our study which is similar to study by Kumari S et al from Andhra Pradesh who reported 18% of Hellp syndrome in their study.…”
Section: Discussionsupporting
confidence: 90%
“…It has been observed that the newborns delivered to females diagnosed with eclampsia, 46.5% were small for gestational age while 25.6% had intrauterine death and 34.88% had neonatal mortality. The overall perinatal mortality was 60.5% [17].…”
Section: Discussionmentioning
confidence: 95%
“…The high perinatal mortality was mostly due to prematurity, which was also supported by other studies conducted in Lahore, Faisalabad, India and Africa 2 . Such neonates are prone to develop bronchopulmonary dysplasia, intra cranial hemorrhage, sepsis and respiratory distress secondary to surfactant defiency 15 . Long term follow up for these babies is required to look for sequel of prematurity [16][17][18][19][20] .…”
Section: Mgso4 Was Included In National Essential Drugmentioning
confidence: 99%